Influence of Shallow and Deep-Aqua Aerobic Exercises on Maximal Oxygen Consumption Parameter Tested to College Men Students - Mohana Krishnan , R. (Journal of Neonatal Surgery, 2025)
The current study set out to investigate the effects of aerobic exercises in shallow and deep water on the maximal oxygen consumption metric given to male college students. The objective of this research was accomplished in 2023–2024 when 45 college male students were chosen from North Chennai Swimming Academy in Chennai, Tamil Nadu. The age range of the subject is 17–23. Three equal groups of 15 subjects each were formed from the chosen subjects: the two experimental groups and a control group of undergraduates. For six weeks, the testing groups I and II engaged in deep aqua aerobic exercise (DAAG) and shallow aqua aerobic activity (SAAG), correspondingly. Throughout the trial, there was no exercise performed by the control group. The study's primary outcome was the maximal oxygen consumption measured using Cooper's formulas and, in turn, the Cooper 12-Minute Run/Walk Assessment. Before the six-week exercise session, a pre-test was administered, and right after, a post-test was measured. The analysis of covariance (ANCOVA) was utilized to determine the F ratio after the data gathered from the three groups was statistically examined for significance. The matched mean differences are ascertained by applying the Scheffe's test as a post-hoc test. The significance level will be set at the 0.05 level of confidence for every instance.